Workforce Development : Matching Education Systems to Workforce Needs - World Bank (World Bank, Washington, DC, 2017)
Equipping national workforces with job-relevant skills is a continuing challenge, and mismatches are a present concern. Many school graduates cannot find jobs commensurate with their education and training. Employers complain of difficulty in filling vacancies and bemoan the scarcity of soft skills for boosting productivity. More broadly, skills constraints make it difficult for companies to innovate and invest in more lucrative economic areas. A goal of SABER-Workforce Development is to help countries improve their workforce development framework.